2018
DOI: 10.3390/ijms19124071
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Stimulates Histone H3 Acetylation, 8-Isoprostane Production, RANKL Expression, and Regulated Osteoprotegerin Expression/Secretion in MG-63 Osteoblastic Cells

Abstract: Butyric acid as a histone deacetylase (HDAC) inhibitor is produced by a number of periodontal and root canal microorganisms (such as Porphyromonas, Fusobacterium, etc.). Butyric acid may affect the biological activities of periodontal/periapical cells such as osteoblasts, periodontal ligament cells, etc., and thus affect periodontal/periapical tissue destruction and healing. The purposes of this study were to study the toxic effects of butyrate on the matrix and mineralization marker expression in MG-63 osteob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Previous studies have found the stimulation of Smad2/3, ERK and p38 signalling pathways by TGF‐β1 in dental pulp cells (Wang et al ). TGF‐β1 may activate Smad2, MEK/ERK and TAK1 phosphorylation in dental pulp cells and SCAP, suggesting its role in regulation of SCAP bioactivity (Chang et al , ). Thus, the role of ALK5/Smad2 and MEK/ERK signallings in regulation of plasminogen activation systems of SCAP was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found the stimulation of Smad2/3, ERK and p38 signalling pathways by TGF‐β1 in dental pulp cells (Wang et al ). TGF‐β1 may activate Smad2, MEK/ERK and TAK1 phosphorylation in dental pulp cells and SCAP, suggesting its role in regulation of SCAP bioactivity (Chang et al , ). Thus, the role of ALK5/Smad2 and MEK/ERK signallings in regulation of plasminogen activation systems of SCAP was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Culture medium was collected for measurement of PAI‐1, uPA and suPAR concentrations by ELISA kits (R & D Systems, Minneapolis, MN, USA) according to the manufacture’s instruction (Chang et al ). Cell number was estimated by 3‐(4,5‐dimethyldiazol‐2‐yl)‐2,5 diphenyl tetrazolium bromide (MTT, Sigma‐Aldrich) assay as described before (Chang et al , , ). In short, MTT was added to SCAP cell culture at a final concentration of 0.5 mg mL −1 and incubated for 2 h. Cultured medium was decanted and then insoluble formazan generated by mitochondrial dehydrogenase of viable SCAP was eluted by 300 μL of DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested three different concentrations for each HDACi (Supplementary file 2) and selected the maximum dose and timing of exposure ensuring acceptable LCLs survival (data not shown). Cells were incubated with vehicles (H2O or DMSO) at maximum time (24h), TSA 2µM for 2h, SAHA 2µM for 24h, VPA 2mM for 24h or NaB 5mM for 24h as suggested from the literature (Supplementary file 2) (Chang et al, 2018;Chriett et al, 2019;Freese et al, 2019;Gottlicher M et al, 2001;Schölz et al, 2015;Tarasenko et al, 2018).…”
Section: Cell Culturesmentioning
confidence: 99%
“…2,3 Butyrate, a well-known histone deacetylase inhibitor, has been shown to be a regulator of osteoblast and osteoclast metabolism. 4,5 In vivo, butyrate increased bone mass in mice by inhibiting osteoclast differentiation and bone resorption through metabolic reprogramming of osteoclasts. 5 Because butyrate stimulates Tregs and Tregs are needed for the bone anabolic activity of PTH, the group of Roberto Pacifici decided to examine the roles of the microbiota and butyrate in the regulation of bone responses to intermittent PTH administration.…”
mentioning
confidence: 99%